The ancient ways of Wessex : travel and communication in an early medieval landscape - Langlands, Alex (Windgather Press, 2019)
The Ancient Ways of Wessex tells the story of Wessex's roads in the early medieval period, at the point at which they first emerge in the historical record. This is the age of the Anglo-Saxons and an era that witnessed the rise of a kingdom that was taken to the very brink of defeat by the Viking invasions of the ninth century. It is a period that goes on to become one within which we can trace the beginnings of the political entity we have come to know today as England. In a series of ten detailed case studies the reader is invited to consider historical and archaeological evidence, alongside topographic information and ancient place-names, in the reconstruction of the networks of routeways and communications that served the people and places of the Anglo-Saxon kingdom of Wessex. Whether you were a peasant, pilgrim, drover, trader, warrior, bishop, king or queen, travel would have been fundamental to life in the early middle ages and this book explores the physical means by which the landscape was constituted to facilitate and improve the movement of people, goods and ideas from the seventh through to the eleventh centuries. What emerges is a dynamic web of interconnecting routeways serving multiple functions and one, perhaps, even busier than that in our own working countryside. A narrative of transition, one of both of continuity and change, provides a fresh and alternative window into the everyday workings of an early medieval landscape through the pathways trodden over a millennium ago.